2011
DOI: 10.1089/acm.2010.0400
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Corporate Chair Massage Program on Musculoskeletal Discomfort and Joint Range of Motion in Office Workers

Abstract: On-site massage sessions twice per week for 1 month are the most effective interventions (compared to one session or no massage intervention) for decreasing the duration of musculoskeletal ache, pain, or discomfort and for increasing range of motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
1
10
0
3
Order By: Relevance
“…It is a fact that drivers belong to the group of occupations with the greatest risk of pain (12), because low back pain is more common among those workers who practice their profession in sitting positions, unlike those who work and have changeable rotating body positions (12,13). Professional drivers are at greater risk for developing low back pain because they are exposed to whole-body vibration, forced positions and handling of goods (14,15). Alperovitch et al (16) found that 45.4% of bus drivers experience low back pain within 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…It is a fact that drivers belong to the group of occupations with the greatest risk of pain (12), because low back pain is more common among those workers who practice their profession in sitting positions, unlike those who work and have changeable rotating body positions (12,13). Professional drivers are at greater risk for developing low back pain because they are exposed to whole-body vibration, forced positions and handling of goods (14,15). Alperovitch et al (16) found that 45.4% of bus drivers experience low back pain within 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…This form of massage is often combined with health education and advice concerning workplace ergonomics and can be performed, for instance, in the workplace, where people are at risk of mus cu loskeletal overload mainly in the region around the spine and in the upper limbs. This issue has already been studied by other authors, who also indicated its therapeutic importance with respect to psychoso matic health [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 90%
“…w miej scu pra cy, tam gdzie oso by na ra żo ne są na prze cią że nia na rzą du ru chu, przede wszyst kim okolic krę go słu pa i koń czyn gór nych. Ba da nia na ten temat prze pro wa dzi li już in ni au to rzy, wska zu jąc również na zna cze nie te ra peu tycz ne w aspek cie zdro wia psy cho so ma tycz ne go [13][14][15][16][17][18][19].…”
Section: Wstępunclassified
See 1 more Smart Citation
“…Several of the patient's conditions were caused by the automobile accident and several massage helps increase range of motion (ROM), decrease hypertonicity of soft tissue, diminish pain or discomfort levels, and renew muscular flexibility. (12) Chair massage has demonstrated, in one study, to improve pain severity in patients with pre-existing musculoskeletal discomfort. (13) With ingenuity, most bodily complaints can be addressed with chair massage, making the massage chair ideal for treatment in remote rural areas.…”
Section: Treatment Rationalementioning
confidence: 99%